Forage Fact Sheet Kudzu - Proyecto Insignia Competitividad y Sustentabilidad de Cadenas Agrícolas (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
Brief explanation of the Kudzu: plant description, forage management, cultivation, cutting, transplanting, fertilization and use